Problematika Guru Pendidikan Agama Islam Di Madrasah - Nevi Nevi; Teddy Sutandy (Journal Education And Islamic Studies, 2024)
This study aims to review the challenges faced by Islamic Education teachers in madrasahs, with the hope of advancing and developing education in these institutions. Education plays a crucial role in shaping individuals with comprehensive competencies, encompassing both attitudes and knowledge. The descriptive method is employed to identify the issues and their solutions. The findings reveal that insufficient human resources are a significant obstacle in enhancing the competencies required by learners. Islamic Education teachers encounter challenges in lesson planning, creating teaching agendas, and effectively and patiently educating students. Proficiency in technology among teachers is also crucial for acquiring additional knowledge and accelerating the dissemination of information relevant to madrasah needs. Consequently, madrasahs can enhance the competencies of their students. This research provides recommendations for enhancing institutional support, providing ongoing training, and reducing the administrative burden on teachers to improve the professionalism and effectiveness of Islamic Education teachers in madrasahs.